![\begin{gathered} \text{x }-(7x)/(6)-(13z)/(6)\text{ = 5} \\ 2x+9y-10z=10 \\ 7x-12y-15z=42 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/xk96agm6ax6usjs8sbn6zk0pwxlaua1vxs.png)
Step-by-step explanation:
6x - 7y - 13z = 30 ...equation 1
2x + 9y - 10z = 10 ...equation 2
7x - 12y - 15z = 42 ...equation 3
Multiply the 1st equation by 1/6:
![\begin{gathered} (1)/(6)(6x\text{ - 7x - 13z = 30)} \\ =\text{ }(6x)/(6)-(7x)/(6)-(13z)/(6)=(30)/(6) \\ =\text{ x }-(7x)/(6)-(13z)/(6)\text{ = 5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n6ku21eya0qo3qiahwsqyb1uhapc47dm9r.png)
Since the multiplication is only applied to the 1st equation, the other equations will remain the same.
It becomes:
![\begin{gathered} \text{x }-(7x)/(6)-(13z)/(6)\text{ = 5} \\ 2x\text{ + 9y - 10z = 10} \\ 7x\text{ - 12y - 15z = 42} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/amefb5h1bg9cnc4kg59y9bq25aqvl0loyp.png)